Smart Domestic Gas Leakage Detection using IOT - M.U. Bharath, G.Balasubramanian, P. Visalakshi (International Journal of Advanced Science and Technology, 2020)
In recent years there has been rapid development in technology which has made human life easier in several aspects. LPG is a need of every household but many accidents happen every year due to domestic gas leakage, so it should be used carefully. As safety and security is the most important factor we have proposed a LPG leakage detection and smart gas booking system. In our daily life, we don’t know exactly the status of LPG gas completion which leads to inconvenience. Along with the leakage detection we also designed feature of sending message to user about the cylinder requirement. In this system MQ-2 is gas sensor used to sense the LPG leakage gas and has high sensitivity to LPG and also response to natural gas. It offers quick response time and accurate detection. The additional advantage of the system is that it continuously monitors the level of the LPG present in the cylinder using level sensors and reduces the work load of gas agency.” Keywords: Alarming framework, LPG and Propane, Things Speak Cloud.